2016
DOI: 10.3233/jad-150890
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Profile and its Association with Neuroimaging Markers of Non-Demented Cerebral Amyloid Angiopathy Patients in a Stroke Unit

Abstract: Non-demented patients with CAA had cognitive deficits in multiple areas. Lower TBV was related to slower processing speed and worse executive function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
61
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(66 citation statements)
references
References 44 publications
4
61
1
Order By: Relevance
“…Our literature reviews found only one other paper which systematically assessed neuropsychological test performance in living CAA patients. 28 Concordant with our findings, processing speed and executive function were the most impaired compared with controls. 28 We extend on these prior findings by providing the first comparisons with AD, MCI, and IS patients.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Our literature reviews found only one other paper which systematically assessed neuropsychological test performance in living CAA patients. 28 Concordant with our findings, processing speed and executive function were the most impaired compared with controls. 28 We extend on these prior findings by providing the first comparisons with AD, MCI, and IS patients.…”
Section: Discussionsupporting
confidence: 79%
“…28 Concordant with our findings, processing speed and executive function were the most impaired compared with controls. 28 We extend on these prior findings by providing the first comparisons with AD, MCI, and IS patients. Our findings may be generalized to living patients with CAA-related syndromes; however, in our study, we may have underestimated the severity of cognitive impairment in symptomatic CAA patients because we excluded CAA patients with dementia, aphasia, or visual field deficits, and many CAA patients with ICH do not survive or have severe disabilities and therefore would either not meet eligibility criteria for our study or potentially be less likely to participate.…”
Section: Discussionsupporting
confidence: 79%
“…Both WMH and MTA are increasingly recognized as core Alzheimer's disease features and as a manifestation of CAA [30]. We found a gradient in WMH extension in all groups [31], but we also found more extended WMH in those subjects fulfilling the mBCAA criteria.…”
Section: Discussionmentioning
confidence: 51%
“…; Xiong et al . ) in the absence of clinically symptomatic stroke. In light of this new evidence, it is now appropriate to consider whether CAA is a neurodegenerative disease, as well as a common cause of stroke.…”
mentioning
confidence: 99%